(untitled) (Economics and region, 2024)
The impact of the quality of working conditions in private companies on the realization of labor potential is very relevant in the modern dynamic and interconnected world. This issue is important because of its profound implications for individuals, organizations and society as a whole. The welfare of workers is at the forefront of this discussion. Working conditions cover a wide range of factors, including workplace safety, job security, fair compensation, and opportunities for personal and professional development. When these conditions are favorable, employees are more likely to thrive, leading to increased job satisfaction, higher morale, and improved mental and physical health. Conversely, poor working conditions can prevent employees from realizing their potential, resulting in reduced productivity and a negative impact on individuals’ lives in general. The topic is relevant in the context of organizational activity. Private companies that prioritize the quality of working conditions tend to get many advantages. Satisfied employees are more engaged, innovative and loyal to their employers. This translates into higher productivity, lower turnover rates and a competitive advantage in attracting top talent. As a result, a company’s income is significantly affected by the extent to which its employees can realize their labor potential. The discussion of working conditions goes beyond individual companies. It is intrinsically linked to wider social and ethical considerations. Providing employees with safe and decent working conditions is consistent with the principles of social responsibility and ethical business practices. Companies that neglect this responsibility can face reputational damage and legal consequences, highlighting the broader societal implications of this issue. The research focuses on the workforce working in private companies in Azerbaijan and how their working conditions affect their ability to fully utilize their skills and potential. The subject of the study is the relationship between the quality of working conditions and the extent to which employees working in private companies in Azerbaijan can use and manifest their labor potential. Different methods were used during the research. These were various methods such as research, analysis, synthesis, comparison, generalization, statistical analysis, survey organization and analysis, data collection. These methods are designed to assess the current state of working conditions in private companies in Azerbaijan. Through the method of synthesis, it was used to make individual elements (properties, attributes) into a single whole for a more detailed study. The information base of the study was made up of various local and foreign research works, survey data, internet resources and books related to the topic. Studying the effect of working conditions on labor potential in private companies has important practical implications for various stakeholders. Private companies can use these findings to optimize their workplaces and improve employee well-being, job satisfaction, and productivity. By investing in better working conditions, such as ergonomic facilities, health and safety measures, and employee development programs, businesses can reduce turnover rates, improve overall workforce performance, and ultimately achieve greater competitiveness and profitability.